(untitled) (Research, Society and Development, 2020)
The interactions in mixed tree plantations, between acacia and eucalyptus and other species, have been addressed mainly regarding the nutritional benefits added to the soil. Information on changes in the constitution of the wood generated in these plantations is essential to help the general understanding of this cultivation system. The objective was to evaluate changes in the physicochemical and anatomical properties of Acacia mangium and Eucalyptus grandis x Eucalyptus urophylla wood, under different levels of mixed and pure planting. The experiment was implemented in the Santana do Paraíso region - MG. Five trees were harvested from each of the six planting conditions (pure eucalyptus and acacia and 4 different proportions of acacia trees), totaling 50 trees at 75 months of age. The variables evaluated were bark, sapwood, heartwood, basic wood density, total lignin, extract, length and thickness of the fiber wall, diameter and frequency of vessels. The contents of bark, heartwood, and sapwood did not change with the planting conditions for both species. Mixed planting with acacia influenced eucalyptus wood in terms of density and total lignin content. In turn, the acacia wood showed changes in its anatomy, which can be considered as adaptive measures derived from its rusticity. The acacia and eucalyptus species responded differently to the growing conditions in a mixed planting, however, the acacia wood was the most stable in terms of the properties studied.